Impact of issuing certificates accountants as evidence during court processes within public sector entities (2015)
The civil service is the backbone of public finances of a state, and therefore what is sought is the efficient control of resources obtained for the development of various projects and plans that the state, regardless of sector to which they are directed. Also within the legal framework and the legal ground of public administration must take into account all the rules and all the regulations to avoid mistakes due to ignorance or omission of these.